AN ANALYSIS OF SOCIAL CONFLICT IN THE MOVIE “BOHEMIAN RHAPSODY” - Bejo Sutrisno; Rieka Endah Purnama; Budi Rachmawati (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
The purpose of this study is to find out the type of conflict faced by the main actor and the source of the conflict and analyze how the main actor resolves the conflict. Objectives the study: (1) to find out the social issues in Bohemian Rhapsody film, (2) to find out the cause conflict in Bohemian Rhapsody film, (3) to find out the solution in Bohemian Rhapsody, the researcher uses descriptive qualitative method in collection the data. The researcher found cause of social conflict were relation to society, human society needs, and identifier. By learning the causes of social conflicts as well as how the character resolves its social conflicts. Besides that, the writer finds that every conflict has its own. There should be ways to overcome the problem. The writer hopes that conflict in the movie can motivate the audience to know the conflict, how to manage and solve the conflict. In this research, the researcher concludes of social conflict can be happened in society like accommodate, avoid, collaborate, and compromise. Keywords: Social conflict, causes, resolve.